Multiscale bone quality analysis in osteoarthritic knee joints reveal a role of the mechanosensory osteocyte network in osteophytes - Rabelo, Gustavo Davi; vom Scheidt, Annika; Klebig, Felix; Hemmatian, Haniyeh; Citak, Mustafa; Amling, Michael; Busse, Björn; Jähn, Katharina (Scientific reports, 2020)
Osteophytes - bony outgrowths on joint structures - are found in healthy individuals but are specifically present in late osteoarthritis (OA). Osteophyte development and function is not well understood, yet biomechanical stimuli are thought to be critical. Bone adapts to mechanical forces via the cellular network of osteocytes. The involvement of osteocytes in osteophyte formation and maturation has not been unravelled. Forty-three osteophytes from tibias of 23 OA patients (65 ± 9 years) were analysed. The trabecular bone structure of osteophytes presented with fewer trabeculae of lower bone mineral density compared to subchondral bone. We identified 40% early stage and 60% late stage osteophytes that significantly differed in their trabecular bone characteristics. Osteophyte bone revealed a higher number of osteocytes and a lower number of empty osteocyte lacunae per bone area than the subchondral bone. We found that OA osteophytes consist of younger bone material comprised of woven and lamellar bone with the capacity to develop into a late stage osteophyte potentially via the involvement of the osteocyte network. Our analysis of OA osteophytes implies a transition from woven to lamellar bone as in physiological bone growth within a pathological joint. Therefore, osteophyte development and growth present a valuable research subject when aiming to investigate the osteogenic signalling cascade.